Investigation into Optimal Conditions for Enzymatic Hydrolysis of Cassava Starch to Glucose by Amylase from Rice (American Journal of Smart Technology and Solutions, 2023)
The challenge of finding locally available materials in abundance to meet up with the increase in demand for glucose syrup necessitated this study. Enzymatic hydrolysis of cassava starch to glucose using glucose amylase sourced from rice was conducted. A-3 factor with 6 levels factorial viz. substrate concentration (0.5, 1.0, 1.5, 2.0, 2.5 and 3.0% w/v), pH (4, 5, 6, 7, 8 and 9) and temperature (30, 40, 50, 60, 70 and 80 °C) experiment were employed. Rice malt was prepared and enzyme activated. Starch (substrate), buffer solutions, standard glucose solution and its calibration curve were also prepared. Starch was hydrolyzed by α-amylase and tested for presence of reducing sugar using Benedict solution. Time course of the reaction was studied and enzyme activity determined. It was observed that as reaction time increased (t), amount of glucose produced [P] initially increased but soon recorded infinitesimal increase and later assumed constant. The effects of substrate concentration, pH and temperature were found to be essential on glucose production. Statistical analysis on the effect of substrate concentration [S], reaction time and their interactions showed significant impact at probability level of (p) = 0.05.